2002
DOI: 10.1126/science.1068206
|View full text |Cite
|
Sign up to set email alerts
|

Optical Projection Tomography as a Tool for 3D Microscopy and Gene Expression Studies

Abstract: Current techniques for three-dimensional (3D) optical microscopy (deconvolution, confocal microscopy, and optical coherence tomography) generate 3D data by "optically sectioning" the specimen. This places severe constraints on the maximum thickness of a specimen that can be imaged. We have developed a microscopy technique that uses optical projection tomography (OPT) to produce high-resolution 3D images of both fluorescent and nonfluorescent biological specimens with a thickness of up to 15 millimeters. OPT mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
919
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,104 publications
(925 citation statements)
references
References 14 publications
2
919
0
4
Order By: Relevance
“…The technique was originally termed optical projection tomography [14][15][16], and was first published as a technique capable of imaging cleared and fixed tissues, but was later also applied to microscopic samples in vivo [17][18][19][20]. Image formation is based on using mathematical models to reconstruct optical contrast within the medium being imaged, an approach capable of imaging fluorescence and absorption.…”
Section: Projection Tomographymentioning
confidence: 99%
“…The technique was originally termed optical projection tomography [14][15][16], and was first published as a technique capable of imaging cleared and fixed tissues, but was later also applied to microscopic samples in vivo [17][18][19][20]. Image formation is based on using mathematical models to reconstruct optical contrast within the medium being imaged, an approach capable of imaging fluorescence and absorption.…”
Section: Projection Tomographymentioning
confidence: 99%
“…OPT (Sharpe et al, 2002) was introduced as an alternative optical method to fluorescence microscopy and overcomes the limitation of the specimen thickness. OPT generates data by acquiring many views of the same specimen at different rotation angles then assembled to create a 3D volume (Fig.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…A second method used for 3D reconstruction of embryonic tissue is optical projection tomography (OPT; Sharpe et al, 2002; Table 1). OPT can also record 3D expression patterns and has the added advantage that the embryo is left in tact.…”
Section: Analysis Of Expression Patterns and Tissue Morphologymentioning
confidence: 99%
“…Improvements to reconstruction algorithms recently have been reported that decrease the contribution from various types of noise associated with image acquisition (Walls et al, 2005). Scatter still reduces the spatial resolution one can achieve with this method (Sharpe et al, 2002), compared with other forms of light microscopy, but the benefit of having a complete 3D volume from a sample 1-10 mm thick (typical; several centimeters maximum, R. Henkelman, personal communication) is worth this sacrifice in many cases.…”
Section: Analysis Of Expression Patterns and Tissue Morphologymentioning
confidence: 99%